Novel synthesis of Azadirachta indica and Chamaecostus cuspidatus formulation mediated calcium oxide nanoparticles incorporated in suture material - Raaj, T Arun; R, Subhashree.; Rajeshkumar, S; N, Thiyaneswaran; Selvaganesh, Sahana (Journal of Neonatal Surgery, 2025)
Background: Suturing for a patient with diabetes undergoing dental implants or any other surgical procedure requires careful consideration and management to prevent complications. Diabetes can affect wound healing and increase the risk of infection, so it's important to take certain precautions when suturing a diabetic patient. Aim: To access the antimicrobial, anti-inflammatory, antioxidant, cytotoxic and embryonic toxicology properties of Azadirachta indica and Chamaecostus cuspidatus formulation mediated calcium oxide nanoparticles incorporated in suture material. Materials and methods: The plant extracts of Azadirachta indica and Chamaecostus cuspidatus formulation mediated calcium oxide nanoparticles incorporated in suture material. This suture material was subjected to antimicrobial, anti-inflammatory, antioxidant, cytotoxic and embryonic toxicology assays. Further, the nanoparticles were characterized using a U-V visible spectrophotometer. Results: The formed nanoparticles showed the highest zone of inhibition for Enterococcus faecalis, followed by Candida albicans and Staphylococcus aureus, whereas Pseudomonas had a lower zone of inhibition. They also possess anti-inflammatory, and antioxidant activity and also prove to be biocompatible. It showed no malformation in embryonic toxicology. Conclusion: The insulin-coated suture material is a type of medical device that combines two functions: suturing of tissues and delivery of insulin. Diabetes patients often require surgical procedures, and this device aims to simplify the post-operative management of these patients.